Calmodulin-Dependent Kinase Kinase/Calmodulin Kinase I Activity Gates Extracellular-Regulated Kinase-Dependent Long-Term Potentiation - Schmitt, John M. (J Neurosci, 2005)
Intracellular Ca(2+) and protein phosphorylation play pivotal roles in long-term potentiation (LTP), a cellular model of learning and memory. Ca(2+) regulates multiple intracellular pathways, including the calmodulin-dependent kinases (CaMKs) and the ERKs (extracellular signal-regulated kinases), both of which are required for LTP. However, the mechanism by which Ca(2+) activates ERK during LTP remains unknown. Here, we describe a requirement for the CaMK-kinase (CaMKK) pathway upstream of ERK in LTP induction. Both the pharmacological inhibitor of CaMKK, STO-609, and dominant-negative CaMKI (dnCaMKI), a downstream target of CaMKK, blocked neuronal NMDA receptor-dependent ERK activation. In contrast, an inhibitor of CaMKII and nuclear-localized dnCaMKIV had no effect on ERK activation. NMDA receptor-dependent LTP induction robustly activated CaMKI, the Ca(2+)-stimulated Ras activator Ras-GRF1 (Ras-guanyl-nucleotide releasing factor), and ERK. STO-609 blocked the activation of all three enzymes during LTP without affecting basal synaptic transmission, activation of CaMKII, or cAMP-dependent activation of ERK. LTP induction itself was suppressed ∼50% by STO-609 in a manner identical to the ERK inhibitor U0126: either inhibitor occluded the effect of the other, suggesting they are part of the same signaling pathway in LTP induction. STO-609 also suppressed regulatory phosphorylation of two downstream ERK targets during LTP, the general translation factors eIF4E (eukaryotic initiation factor 4) and its binding protein 4E-BP1 (eukaryotic initiation factor 4E-binding protein 1). These data indicate an essential role for CaMKK and CaMKI to link NMDA receptor-mediated Ca(2+) elevation with ERK-dependent LTP.